2015
DOI: 10.7554/elife.08698
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of AMPK signaling by ROQUIN promotes T follicular helper cell formation

Abstract: T follicular helper cells (Tfh) are critical for the longevity and quality of antibody-mediated protection against infection. Yet few signaling pathways have been identified to be unique solely to Tfh development. ROQUIN is a post-transcriptional repressor of T cells, acting through its ROQ domain to destabilize mRNA targets important for Th1, Th17, and Tfh biology. Here, we report that ROQUIN has a paradoxical function on Tfh differentiation mediated by its RING domain: mice with a T cell-specific deletion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 105 publications
(161 reference statements)
2
52
0
Order By: Relevance
“…In contrast, hampered antigen-specific Tfh response was observed in mice with T cells specific deletion of Roquin RING domain depicting Roquin RING domain positively regulates Tfh differentiation. Mechanistically, Roquin directly binds with AMPKα subunit and thus represses adenosine monophosphate-activated protein kinase (AMPK) activity (137). …”
Section: Ubiquitin E3 Ligasementioning
confidence: 99%
“…In contrast, hampered antigen-specific Tfh response was observed in mice with T cells specific deletion of Roquin RING domain depicting Roquin RING domain positively regulates Tfh differentiation. Mechanistically, Roquin directly binds with AMPKα subunit and thus represses adenosine monophosphate-activated protein kinase (AMPK) activity (137). …”
Section: Ubiquitin E3 Ligasementioning
confidence: 99%
“…110 However, Roqin , which controls the expression of a number of genes involved in Tfh diferentiation, 111 blocks AMP-activated protein kinase (AMPK) activation, leading to mTORC1 activation, which is required for Tfh development. 112 In addition, mTORC2 activation has been indirectly shown to be linked to Tfh diferentiation. 113 Recent studies have found that retention of activated mTORC1 during asymmetric cell division in CD8 + T cells bestow the daughter cell with effector functions, whereas the mTORC1 low daughter cell acquires memory properties.…”
Section: Cd4+ T Cells In Slementioning
confidence: 99%
“…29 Glutaminolysis is essential to sustain T-cell activation and proliferation. 138, 139 Blocking use of glutamine with the drug 6-diazo-5-oxo- l -norleucine (DON) inhibits activation-induced proliferation in vitro as well as in response to immunization with a nominal antigen. 138 In addition, DON treatment in combination with glucose inhibition was very effective in preventing allograft rejection through the inhibition of inflammatory T cells.…”
Section: Cd4+ T Cells In Slementioning
confidence: 99%
“…Whether the zinc finger domain contributes to Roquin’s RNA binding activity is currently unknown. The RING domain is an E3 ubiquitin ligase that autoubiquitinates Roquins (17). While an in vivo requirement for Roquin-2’s RING domain was not immediately apparent, germline deletion of Roquin-1’s RING domain resulted in perinatal lethality (18).…”
mentioning
confidence: 99%
“…While an in vivo requirement for Roquin-2’s RING domain was not immediately apparent, germline deletion of Roquin-1’s RING domain resulted in perinatal lethality (18). The RING domain was proposed to downregulate 5′ adenosine monophosphate-activated protein kinase α1 (Ampkα1) levels through a protein-protein interaction independently of its mRNA binding activity (17) suggesting multiple modes of Roquin function. In turn, hypoactive Ampkα1 causes increased mTOR signaling and mRNA translation leading to enhanced T follicular helper (Tfh) cell differentiation.…”
mentioning
confidence: 99%